2022
DOI: 10.3389/ftox.2022.936149
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide induces rapid thiol oxidation that leads to ferroptosis in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is both a devastating and common disease. Every year in the United States, about 24,500 men and 10,000 women are diagnosed with HCC, and more than half of those diagnosed patients die from this disease. Thus far, conventional therapeutics have not been successful for patients with HCC due to various underlying comorbidities. Poor survival rate and high incidence of recurrence after therapy indicate that the differences between the redox environments of normal surrounding liver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A more recent study in hepatocellular carcinoma cells showed that parthenolide depleted intracellular thiols (e.g., GSH) by increasing cytosolic and mitochondrial thiol oxidation, leading to early mitochondrial dysfunction and oxidative stress. This was accompanied by an increase in lipid peroxidation leading to ferroptosis, an irreversible mechanism of cell death [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study in hepatocellular carcinoma cells showed that parthenolide depleted intracellular thiols (e.g., GSH) by increasing cytosolic and mitochondrial thiol oxidation, leading to early mitochondrial dysfunction and oxidative stress. This was accompanied by an increase in lipid peroxidation leading to ferroptosis, an irreversible mechanism of cell death [10].…”
Section: Discussionmentioning
confidence: 99%
“…Parthenolide is a naturally occurring sesquiterpene lactone isolated from feverfew (Tanacetum parthenium), a traditional medicinal plant that has been conventionally used in the treatment of fever, migraines, and arthritis. Parthenolide has also been highly studied for its anticancer activities in multiple cancer types, including hepatocellular carcinoma, breast cancer, and hematological malignancies [10][11][12][13][14][15][16], among others. The variety of biological activities associated with parthenolide are mainly related to its chemical structure, which includes an α-methylene-γ-lactone ring and epoxide group capable of interacting with the nucleophilic sites of various proteins, ultimately interfering with different signaling pathways (Figure 1) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pien-Tze-Huang, a Chinese patent medicine approved by China Food and Drug Administration, may effectively improve the microenvironment of LF and inhibit the occurrence of HCC through triggering ferroptosis of tumor cells via suppressing the SLC7A11-GSH-GPX4 axis [228]. Moreover, rhamnazin [229], polyphyllin VI [230], corosolic acid [231], solasonine [232], parthenolide [233], cryptotanshinone [234], and heteronemin [235] could trigger ferroptosis in HCC cells through down-regulating GPX4 expression. Among them, parthenolide, cryptotanshinone, corosolic acid, and solasonine could also inhibit the synthesis of GSH by rapid thiol oxidation [233] and reducing the expression of SCL7A11 [234] and glutathione synthetase (GSS) [231,232], respectively.…”
Section: Artesunatementioning
confidence: 99%
“…Moreover, rhamnazin [229], polyphyllin VI [230], corosolic acid [231], solasonine [232], parthenolide [233], cryptotanshinone [234], and heteronemin [235] could trigger ferroptosis in HCC cells through down-regulating GPX4 expression. Among them, parthenolide, cryptotanshinone, corosolic acid, and solasonine could also inhibit the synthesis of GSH by rapid thiol oxidation [233] and reducing the expression of SCL7A11 [234] and glutathione synthetase (GSS) [231,232], respectively. Interestingly, aspirin, a derivative of salicylic acid, could trigger ferroptosis by restricting NF-κB-activated SLC7A11 transcription, thereby inhibiting the growth of HCC [236].…”
Section: Artesunatementioning
confidence: 99%
“…Consistently, in vivo studies have confirmed that corosolic acid inhibits tumor growth by promoting HERPUD1‐mediated ferroptosis (Y. Peng, Li, et al, 2022). Strikingly, parthenolide decreased the levels of intracellular reduced GSH by oxidizing the sulfhydryl group of GSH, thereby enhancing the sensitivity of HCC cells to ferroptosis (LoBianco et al, 2022). These data suggest that the SLC7A11/GSH/GPX4 system is a key target by which terpenoids inhibit cancer progression.…”
Section: Regulation Of Ferroptosis By Natural Productsmentioning
confidence: 99%